2015
DOI: 10.5194/nhess-15-1807-2015
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean cyclone characteristics related to precipitation occurrence in Crete, Greece

Abstract: Abstract. The characteristics of the cyclone tracks that caused precipitation events of variable intensity for the period 1979-2011 over the island of Crete are presented. The data set used for cyclone identification is the 0.5 • × 0.5 • , 30 years European Centre for Medium-Range Weather Forecasts (ECMWF) ERA-Interim mean sea-level pressure. Cyclone characteristics are calculated with the aid of the Melbourne University algorithm (MS scheme). Daily precipitation data from a dense gauging network over the isla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…Several studies have extensively analysed in the past extreme hydro-meteorological phenomena attributed to extreme flow and extreme precipitation in several Mediterranean watersheds in Crete. Iordanidou et al [3] found that the characteristics of cyclone tracks are strongly correlated with variable intensity precipitation in Mediterranean, providing valuable forecasting information on rainfall extremes, which are subsequently strongly related to flood occurrence [4]. Flocas et al [5] analysed the seasonality of historical floods' hydro-meteorological characteristics in Crete, revealing valuable information within the context of flood occurrence in the island.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have extensively analysed in the past extreme hydro-meteorological phenomena attributed to extreme flow and extreme precipitation in several Mediterranean watersheds in Crete. Iordanidou et al [3] found that the characteristics of cyclone tracks are strongly correlated with variable intensity precipitation in Mediterranean, providing valuable forecasting information on rainfall extremes, which are subsequently strongly related to flood occurrence [4]. Flocas et al [5] analysed the seasonality of historical floods' hydro-meteorological characteristics in Crete, revealing valuable information within the context of flood occurrence in the island.…”
Section: Introductionmentioning
confidence: 99%
“…This scheme was chosen because of its proven reliability in capturing the storm centers (closed and open) in the EuroMediterranean region (Simmonds and Keay 2002;Pinto et al 2005;Flocas et al 2010;Syed et al 2010;Nissen et al 2010Nissen et al , 2013Iordanidou et al 2015;Almazroui et al 2016). The MS scheme is used to identify and track storm centers which are having a life cycle of equal or more than 1 day and then performs statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Plenty of studies have focused on hydro-meteorological characteristics of precipitation events [6][7][8][9], as well as on the analysis of flash floods' impacts [10,11], on the island of Crete. Climate change effect is expected to produce more intense and more frequent heavy precipitation events [12].…”
Section: Introductionmentioning
confidence: 99%